1992
DOI: 10.1046/j.1537-2995.1992.32893032102.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial on the efficacy of an autologous blood drainage and transfusion device in patients undergoing elective knee arthroplasty

Abstract: The purpose of the study reported here was the determination of the efficacy of a postoperative autologous blood drainage and transfusion device in reducing allogeneic red cell requirements in patients undergoing elective knee arthroplasty. The study was a randomized controlled trial with adult patients undergoing unilateral elective arthroplastic knee surgery. Patients underwent suction drainage, attached to an autologous blood drainage and transfusion device, or standard suction drainage. Allogeneic red cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 7 publications
2
49
0
2
Order By: Relevance
“…17 Moreover, though A-Plts are thought to be a purer platelet product than WB-Plts with respect to the increased rate of adverse events, sCD40L was increased in these components compared with WB-Plts and thus may have unexpected effects in the transfused host. 41,42 A recent report revealed that sCD40L is associated with adverse events in patients requiring platelet transfusion (in press). 43 Furthermore, sCD40L may have direct Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, though A-Plts are thought to be a purer platelet product than WB-Plts with respect to the increased rate of adverse events, sCD40L was increased in these components compared with WB-Plts and thus may have unexpected effects in the transfused host. 41,42 A recent report revealed that sCD40L is associated with adverse events in patients requiring platelet transfusion (in press). 43 Furthermore, sCD40L may have direct Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the use of blood retrieval in total knee ( Dalen et al, 1996;Gannon et al, 1991;Groh et al, 1990;Handel et al, 2006;Heddle et al, 1992;Hendrych, 2006;Kristensen et al, 1992;Majkowski et al, 1991;Martin et al, 1992;Munoz et al, 2005a;Noain et al, 2005;Simpson et al, 1994;Strumper et al, 2004;Thomas et al, 2001;Wojan et al, 2005;Xenakis et al, 1997) and hip (Gannon et al, 1991;Kristensen et al, 1992) arthroplasty, it is considered to be useful as it decreases blood transfusion necessity, reaching a 48% decrease transfusion requirements. The use of postoperative retrieval in knee or hip primary surgery, analyzed from a costbenefit point of view, is a profitable procedure ( Dramis & Plewes, 2006;Jones et al, 2004;Thomas et al, 2001;Wojan et al, 2005).…”
Section: Use Of Postoperative Blood Retrievalmentioning
confidence: 99%
“…Intraoperative cell salvage has been proven to be an effective method to avoid allogeneic blood transfusion [81]. Indirect autologous transfusion systems in orthopedic patients can decrease the need for allogeneic blood transfusions from 70% to 23% [43]. Due to high cost (Cell Saver® about $2400, Haemo- Another method for replacing shed blood includes reinfusion of postoperative drainage as a form of direct autologous transfusion (e.g., Bellovac ABT®, Astra Tech, Vienna, Austria).…”
Section: Autologous Capture and Transfusionmentioning
confidence: 99%